Sugar Repression of Mannitol Dehydrogenase Activity in Celery Cells. - Prata, RTN. (1997)
We present evidence that the activity of the mannitol-catabolizing enzyme mannitol dehydrogenase (MTD) is repressed by sugars in cultured celery (Apium graveolens L.) cells. Furthermore, this sugar repression appears to be mediated by hexokinases (HKs) in a manner comparable to the reported sugar repression of photosynthetic genes. Glucose (Glc)-grown cell cultures expressed little MTD activity during active growth, but underwent a marked increase in MTD activity, protein, and RNA upon Glc starvation. Replenishment of Glc in the medium resulted in decreased MTD activity, protein, and RNA within 12 h. Addition of mannoheptulose, a competitive inhibitor of HK, derepressed MTD activity in Glc-grown cultures. In contrast, the addition of the sugar analog 2-deoxyglucose, which is phosphorylated by HK but not further metabolized, repressed MTD activity in mannitol-grown cultures. Collectively, these data suggest that HK and sugar phosphorylation are involved in signaling MTD repression. In vivo repression of MTD activity by galactose (Gal), which is not a substrate of HK, appeared to be an exception to this hypothesis. Further analyses, however, showed that the products of Gal catabolism, Glc and fructose, rather than Gal itself, were correlated with MTD repression.